Threatened, rare, and functionally rare species of fish in the Upper Paraná River floodplain: ecological perspectives and conservation. - Nunes, Lucas Machado (2023)
Understanding how the loss of a species is related to its functional role in a community or ecosystem is essential. To explain why some species are more prone to be endangered than others is a major goal of conservation biology. Beyond the loss of a species, the loss of ecological processes that sustain ecosystem functioning can be the most critical influence. To evaluate the threatened, taxonomical, and functional rare species, we used fish data from 2000 to 2019, collected from nine sampling points on the Upper Paraná River floodplain (the large rivers on the floodplain, Ivinheima, Baía and Paraná, and six lakes eventually connected to the rivers: Ventura and Patos lake (Ivinheima River), Guaraná and Fechada Lakes (Baía River), Ressaco do Pau Velho and Garças Lake (Paraná River). Fish were collected using gillnets with different size mesh, and the number of individuals caught as an estimation of abundance. We obtained geographic range, habitat specificity, and population size for the taxonomical rarity index. To estimate the functional rarity, we used eleven functional traits in the composition of a functional distance matrix, together with and relative abundance matrix to obtain Functional Uniqueness and Functional Restrictedness. The outcome was a 58 species list. 76% of the species shared taxonomical and functional rarity, four were endangered, and 17 species are considered exotic to the Upper Paraná River.